Magnetic Field Distribution Detecting and Computing Methods for Experimental Mechanics - KALETA, J.; WIEWIÓRSKI, P. (Engineering Transactions, 2010)
This paper presents the design and measuring potential of the latest generation of the magnetic scanner called Magscanner-Maglab System (MMS) which enables a fast acquisition of 3D signals from magnetic sensors and their visualization as digitalized magnetic images for a variety of flat and cylindrical objects. MMS can be used as entirely autonomous or combined (through common control) with a typical material testing machine for static load and fatigue tests. The system can be used to investigate magnetomechanical phenomena and identify their models in experimental mechanics, as well as detect and locate strain fields, areas of plastic deformations and cracks in industrial processes. It has been used recently to measure the magnetic field around objects subjected to technological processing in order to check their quality.